Photochemotherapy (PUVA): An Overview - Fakir Mohan Debta; Anil Ghom; Priyanka Debta; Abhijeet Deoghare (Wolters Kluwer Medknow Publications, 2010)
Photochemotherapy (PUVA) has become a useful alternative in dermatologic therapy. Start from historical date up to modern era the safe and useful modes of PUVA has been documented in many immunological disorder. Despite side effect and potential long-term hazards photochemotherapy shown in clinical routine as an effective alternative to conventional immunosuppressive therapy. A wide range of diverse field for its possible utility provides an alternative armamentarium in many immunological disorder for dermatologist and also for oral diagnostician.